Laws and rules in Indo-European - Probert, Philomen; Willi, Andreas (Oxford : Oxford University Press, 2012)
Leading scholars from all over the world reassess the operation of the laws and rules in Indo-European which constrain the reconstructions and etymologies on which knowledge of the history and prehistory of the language family is based.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Indo-European languages -- Syntax; Indo-European languages -- Grammar; Historical linguistics